AB0779 Identifying potentially non-adherent rheumatology patients: application of the compliance-questionnaire-rheumatology. (23rd January 2014) - Ingham, M.; Bolge, S.; Kopenhafer, L.
Abstract : Background: The 19 item Compliance-Questionnaire-Rheumatology (CQR) 1 is an open access questionnaire that was developed by Rheumatologists in the Netherlands, to predict the potential for non-adherence specifically in Rheumatology patients. It was validated against gold standard compliance measures. The questionnaire item bank was developed from the literature, home interviews and focus groups. Responses are provided on a 4-point Likert scale delineated by strength of agreement (don't agree at all, don't agree, agree, agree very much). Objectives: To quantify the proportion of respondents that would fall into each adherence risk category when administered on a large scale and to assess the potential for further validation of the questionnaire. Methods: Patients self-reporting a diagnosis of rheumatoid arthritis (RA) and residing in the United States completed a self-administered, internet-based questionnaire in Fall 2011, which included the CQR. CQR data were analysed using an automated analytical tool provided by the developers. Based on the validation paper, individual raw CQR questions are weighted to produce adjusted total summary scores for each patient, which can then be compared to validated cutoff values for specified levels of desired compliance ranging from 50-95%, to establish whether the patient is or is not likely to be non-compliant. Different weights exist depending on whether the user is interested in the potential for "correct dosing" compliance (the percentage of days the correct number of doses were taken) or dose "taking" compliance (the percentage of prescribed doses taken). Results: Survey respondents were 76.2% female, 86.2% Caucasian, with mean age 56.4 years. At the 90%, 80%, and 50% minimum thresholds for "correct dosing" compliance, 99.2%, 83.8% and 66.1% of patients were identified as potentially non-compliant respectively. The respective percentages for dose "taking" compliance, based on the same minimum thresholds, were 91.3%, 67.6% and 16.5% of patients. Conclusions: Depending on desired compliance thresholds, at least 60% of self-reported RA patients demonstrate attributes identifying them as potentially non-compliant with treatment, based on taking the correct daily dose. Fewer patients were identified as potentially non-compliant based on taking the correct number of prescribed doses overall. This instrument may be useful in streaming patients into adherence programs, identifying appropriate patients for specific treatments or improving patient/physician discourse during shared decision making discussions. Future work should look at validating against other common adherence measures and fine tuning patient attributes most likely to lead to non-compliance. References: de Klerk et al; Development of a Questionnaire to Investigate Patient Compliance with Antirheumatic Drug Therapy, 1999. The Journal of Rheumatology; v26(12): pp2635-41.v Disclosure of Interest: M. Ingham Employee of: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, L. Kopenhafer Consultant for: Janssen Scientific Affairs, LLC